2008
DOI: 10.1002/cne.21864
|View full text |Cite
|
Sign up to set email alerts
|

Cervical prephrenic interneurons in the normal and lesioned spinal cord of the adult rat

Abstract: While monosynaptic bulbospinal projections to phrenic motoneurons have been extensively described, little is known about the organization of phrenic premotor neurons in the adult rat spinal cord. As interneurons may play an important role in normal breathing and recovery following spinal cord injury, the present study has used anterograde and transneuronal retrograde tracing to study their distribution and synaptic relations. Exclusive unilateral, first-order labeling of the phrenic motoneuron pool with pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
226
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(244 citation statements)
references
References 81 publications
17
226
0
Order By: Relevance
“…The present findings could influence interpretation of previous studies using PRV to assess neural pathways in intact and spinal cord-injured animals (Bareyre et al, 2004;Kim et al, 2002;Lane et al, 2008;Pan et al, 2005;Yu et al, 2003), including analysis of changes in c-Fos staining after SCI (Im et al, 2008). For example, decreased numbers of neurons observed in autonomic centers after SCI may be attributed to diminished viral uptake, in addition to decreased integrity of motor neuron pathways (Kim et al, 2002).…”
Section: Fig 4 Distribution Patterns Of Prv-152-infected Neurons Inmentioning
confidence: 74%
See 2 more Smart Citations
“…The present findings could influence interpretation of previous studies using PRV to assess neural pathways in intact and spinal cord-injured animals (Bareyre et al, 2004;Kim et al, 2002;Lane et al, 2008;Pan et al, 2005;Yu et al, 2003), including analysis of changes in c-Fos staining after SCI (Im et al, 2008). For example, decreased numbers of neurons observed in autonomic centers after SCI may be attributed to diminished viral uptake, in addition to decreased integrity of motor neuron pathways (Kim et al, 2002).…”
Section: Fig 4 Distribution Patterns Of Prv-152-infected Neurons Inmentioning
confidence: 74%
“…For example, decreased numbers of neurons observed in autonomic centers after SCI may be attributed to diminished viral uptake, in addition to decreased integrity of motor neuron pathways (Kim et al, 2002). Alternatively, complete SCI has little effect on PRV transport below a lesion (Yu et al, 2003), whereas studies with incomplete lesion models do not provide insight about whether reported injuryinduced alterations of neural circuitry are accompanied by attenuated PRV uptake and expression (Bareyre et al, 2004;Lane et al, 2008;Pan et al, 2005). Notably, increases in PRVlabeled spinal neurons are seen weeks to months after complete SCI following bladder inoculation, suggesting a reorganization of the spinal cord circuitry controlling the bladder after injury (Yu et al, 2003).…”
Section: Fig 4 Distribution Patterns Of Prv-152-infected Neurons Inmentioning
confidence: 99%
See 1 more Smart Citation
“…A laparotomy was performed and the abdominal muscle was retracted to expose the diaphragm. Monosynaptic retrograde tracer [40 μl; 0.05%, cholera toxin subunit B (CT-B) conjugated with Alexa Fluor 594 (C34777); ThermoFisher Scientific, Waltham, MA, USA] (n = 4) or trans-synaptic tracer [1.75%, wheat germ agglutinin (WGA) conjugated with Alexa Fluor 594 (W11262); ThermoFisher Scientific] (n = 7) was painted on the bilateral diaphragm [27,28]. At 3 days after tracer painting, the animals were anesthetized with urethane (1.6 g/kg, i.p.)…”
Section: Retrograde Tracer Applicationmentioning
confidence: 99%
“…A detailed understanding of the neuronal circuits underlying spontaneous recovery can significantly contribute to the design of cell-based and axonal growth-promoting approaches, as well as critical evaluation and prediction of their efficacy. 1,2 Unfortunately, comprehensive neuroanatomical demonstrations of functionally defined intraspinal circuits are lacking, in even the intact spinal cord. 1 The more notable exceptions are studies of spinal bladder, 3 autonomic, 4 and respiratory 1,5 networks, which have employed the transneuronal tracer, pseudorabies virus (PRV), to identify pre-motor spinal interneurons.…”
Section: Introductionmentioning
confidence: 99%